The Effect of Social Media Marketing and Product Quality on Purchasing Decisions Through Purchase Interest - Sabrina, Dira; Welsa, Henny; Cahya, Agus Dwi Dwi (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2024)
Scarlett Whitening products are a top choice for women due to their affordability and availability in various beauty stores. The company is smart in utilizing social media marketing to be an effective strategy in advertising products to the modern era that relies on technology. Population in the study were users of Scarlett Whitening products in the Management Study Program of Sarjanawiyata Tamansiswa University. Method used in the research is quantitative, by distributing Google Form questionnaires to 100 respondents. The analysis conducted by classical assumption test and multiple linear regression using SPSS 20.0. The results showed that social media marketing and product quality have a significant positive impact on purchase intention. However, social media marketing does not significantly affect purchasing decisions, but purchasing decisions are significantly positively influenced by product quality. Purchase intention acts as a significant mediator between purchasing decisions, social media marketing, and product quality.